Goth : Undead Subculture - Goodlad, Lauren M. E. (Book collections on Project MUSE., 2007)
Since it first emerged from Britain's punk-rock scene in the late 1970s, goth subculture has haunted postmodern culture and society, reinventing itself inside and against the mainstream. Goth: Undead Subculture is the first collection of scholarly essays devoted to this enduring yet little examined cultural phenomenon. Twenty-three essays from various disciplines explore the music, cinema, television, fashion, literature, aesthetics, and fandoms associated with the subculture. They examine goth's many dimensions - including its melancholy, androgyny, spirituality, and perversity - and take readers inside locations in Los Angeles, Austin, Leeds, London, Buffalo, New York City, and Sydney. A number of the contributors are or have been participants in the subculture, and several draw on their own experiences.